MERCOSUR AND POST-COVID 19 EXIT STRATEGIES IN TERMS OS SUSTAINABLE DEVELOPMENT: RENEWABLE ENERGIES AND CLIMATE CHANGE - Stuhldreher, Amalia Margarita; Morales Olmos, Virginia (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
COVID 19 affected the projection of the SDGs, with debates on a post-pandemic "green" exit. With a multilevel perspective, this paper addresses the evolution of energy policies in MERCOSUR countries, focusing on renewable energies and climate change. Uruguay's case is discussed, in contrast with Argentina and Brazil. Points of convergence in divergent situations are considered, given the commercial exchanges of electric energy between Uruguay and its MERCOSUR partners. Investments in renewable energies in Uruguay, its current situation, and its prospects are analyzed, considering the position of the Block and an eventual scheme of regional climate governance in the future.